Optimalisasi Sanggar Among Lare dalam Rangka Peningkatan Taraf Hidup Masyarakat di Kalurahan Sendangsari, Kapanewon Pengasih, Kabupaten Kulon Progo, Daerah Istimewa Yogyakarta - Prasojo Prihantono; Anggi Rahajeng (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
Tourism is a sector that has an influence on increasing income in an area, including village. In line with the Village Fund Allocation (ADD) and substantial potential, village governments are striving to transform their areas into tourist destinations, one such example is Kalurahan/Village Sendangsari, Pengasih, Kulon Progo. The program also encouraged by the Government of Daerah Istimewa Yogyakarta with a policy named Desa Mandiri Budaya (Cultural-independent Village). This research aims to analyze Sanggar Among Lare in this village and develop strategies to optimize its existence as educational tourism site. This article is the result of participatory observations and interviews from the community empowerment activities (KKN). The optimization strategy carried out by the KKN-PPM UGM YO-107 Team consists of two methods, training activities and policy formulation in the form of policy recommendations for stakeholder. By optimizing its potential, the presence of Sanggar Among Lare is expected to enhance the standard of living for residents in Sendangsari Village.